MANAJEMEN PERPUSTAKAAN DALAM MENINGKATKAN BUDAYA LITERASI DI MAN 3 NGAWI - Akmila, Khilmak; Fikriyani, Afini; Mushoffa, Luluk; Afifa, Lutfi; Amin, Muhammad Yunus Ridho; Anshori, Muchlis (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The background of this study is the low literacy culture among students at MAN 3 Ngawi, which acts as a barrier in the development of learning. This study aims to analyze how library management can effectively improve students' literacy culture. The method used is qualitative with a descriptive approach, involving data collection through interviews, observations, and documentation. The results show that library management includes structured planning, clear organization with task distribution among librarians, teachers, and the vice principal of curriculum, as well as the implementation of innovative literacy programs such as the integration of the library into learning activities and the provision of incentives to students. Routine supervision is also conducted for the evaluation and improvement of library performance. A significant increase in student visits to the library indicates the success of the library management at MAN 3 Ngawi. In conclusion, a well-managed library can become an effective literacy center to enhance students' reading interest and literacy culture.